The voice in the Suzuki Training (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article explores the matter of voice in Tadashi Suzuki's training and directing work, establishing relationships between the fundamentals of the Japanese director's practice and Adriana Cavarero's thoughts on the theme. This work is the result of the interaction between the hands-on experience with Suzuki training and the reflection based on Cavarero's concepts, especially in regards to the aspect of unity and voice's relational and corporeal nature. It has been observed how the voice in Suzuki's training and in his performances ends up being understood in its universal dimension where, without the ties of semantics, the elements of voice can affect and generate interaction with one another - performers and audience.
Keywords: Suzuki training; Tadashi Suzuki; Adriana Cavarero; Voice; Contemporary Theater